An experimental study of double-row floating breakwaters - Ji, Chunyan; Deng, Xiaokang; Cheng, Yong (Journal of marine science and technology, 2019)
A preliminary experimental study on the hydrodynamic behaviors of double-row floating breakwaters is carried out in a wave flume under regular wave action. The floating breakwater chosen as the experimental subject is a dual rectangular pontoon floating breakwater. The hydrodynamic behaviors of the floating breakwater are validated through the calculation of the wave transmission coefficients, the wave reflection coefficients, the motion responses of the floating breakwaters and the mooring forces for different waves and structural parameters. The dynamic responses of single-row floating breakwater as a control group are also examined in the present experiments. The results indicate that double-row floating breakwaters significantly reduces the transmission coefficients as compared with single-row floating breakwater, especially for short-period wave, which is attributed to dissipation caused by eddies and moon-pool effect. However, the reflection performance is almost identical between two types. It is also found that the motion responses of the single-row and double-row floating breakwaters are similar. Spacing distance between double-row floating breakwaters has a significant influence on the windward mooring tension of the model at the upstream location, which always keeps the largest level in all mooring forces.